Peningkatan Pengetahun Kader Kesehatan Tentang Reinventing Benefit Sampah Dalam Upaya Peningkatan Cakupan ASI di Wilayah Desa Caturharjo Srandakan Bantul - Sukismanto, Sukismanto; Fitriana, Lala Budi; Vidayanti, Venny (Universitas Respati Yogyakarta, 2020)
The scope of breast milk (ASI) must always be increased with various effort according to the conditions of the community. Availability of nutritions and limited of funds are the factors that make to increase in the Caturharjo region that exclusive breast milk. One of effort is to teach PKK mothers to be able to reinventing waste benefits. Community service activities with Caturharjo village cadres can reach a wider area and PKK who are always in direct contact with posyandu activities in each hamlet. Activities carried out in the form of conseling and training with direct demonstrations. The results of activities attended by 91 health cadres have given results that there is an increase in the understanding of health cadres mothers about the use waste from average of 7.2 to 8.25 on a scale of 0-10 points. Health cadres are able to carry out breastfeeding correctly and safely. The community expects similar activities with more massive targets up to the hamlet level community in the Caturharjo Srandakan BantulKeyword : breast milk exclusive, Waste reinventing